Enhanced Foot Proprioception Through 3-Minute Walking Bouts with Ultra-Minimalist Shoes on Surfaces That Mimic Highly Rugged Natural Terrains - Andrea Biscarini; Andrea Calandra; Alberto Marcucci; Roberto Panichi; Angelo Belotti (Biomimetics)
The use of minimalist shoes can lead to enhanced foot somatosensory activation and postural stability but can also increase the incidence of overuse injuries during high-impact or prolonged activities. Therefore, it appears useful to explore new strategies that employ minimalist shoes to effectively facilitate the somatosensory activation of the foot while minimizing acute and cumulative joint stress and risk of injury. To this purpose, this study introduces a novel exercise paradigm: walking for three minutes in ultra-minimalist shoes on artificial flat surfaces designed to mimic highly rugged natural terrains. The activity of foot muscles and lumbar multifidus, pain perception level, and stabilometric parameters were recorded and analyzed to characterize the novel exercise, comparing it to walking barefoot or in conventional shoes on the same rugged surface. Compared to being barefoot, ultra-minimalist shoes effectively filter nociceptive stimuli from the rugged surface, while compared to conventional shoes, they enhance the somatosensory input supporting static stability. Walking with ultra-minimalist and conventional shoes yielded higher gastrocnemius activity and lower tibialis anterior and multifidus activity compared to barefoot walking. This study highlights a practical and safe framework for enhancing foot somatosensory activation and postural stability. The new intervention is suitable for people of all ages, requires minimal time commitment, and can be performed in controlled environments such as homes, gyms, and healthcare facilities.